Censored Posterior and Predictive Likelihood in Bayesian Left-Tail Prediction for Accurate Value at Risk Estimation - Lukasz Gatarek; Lennart Hoogerheide; Koen Hooning; Herman K. van Dijk (Tinbergen Institute, 2013)
Accurate prediction of risk measures such as Value at Risk (VaR) and Expected Shortfall (ES) requires precise estimation of the tail of the predictive distribution. Two novel concepts are introduced that offer a specific focus on this part of the predictive density: the censored posterior, a posterior in which the likelihood is replaced by the censored likelihood; and the censored predictive likelihood, which is used for Bayesian Model Averaging. We perform extensive experiments involving simulated and empirical data. Our results show the ability of these new approaches to outperform the standard posterior and traditional Bayesian Model Averaging techniques in applications of Value-at-Risk prediction in GARCH models.
urn:NBN:nl:ui:15-1765/39847
Keywords: C11; C15; C22; C51; C53; C58; G17; 330; censored likelihood; censored posterior; censored predictive likelihood; Bayesian Model Averaging; Value at Risk; Metropolis-Hastings algorithm.; Risikoprämie; Statistische Verteilung; Prognoseverfahren; Bayes-Statistik; ARCH-Modell; Algorithmus; Theorie